2015
DOI: 10.1007/s12687-015-0225-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of personal sickle cell genotype among parents of children with sickle cell disease in southeast Nigeria

Abstract: Sickle cell trait (SCT; HbAS), the heterozygous state for the sickle cell allele of the beta globin gene, is carried by as many as 100 million individuals worldwide. Nigeria has the highest prevalence of SCT, impacting an estimated 25 % of adult population. This study was designed to assess timing of awareness, knowledge of SCT status and preferred method of education among parents of children with sickle cell disease (SCD). We conducted a cross-sectional survey of parents of children with SCD from June 2013-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Our finding of very low awareness of individual haemoglobin genotype status among participants agreed with previous studies from Northern Nigeria, [39,40] but was in contrast with high level of awareness found in Southern Nigeria. [41,42] High acceptability of personal screening for haemoglobin genotype among the participants in this study was in keeping with earlier studies in Nigeria [39,43] though poor participation in screening program has also been documented [44].…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of very low awareness of individual haemoglobin genotype status among participants agreed with previous studies from Northern Nigeria, [39,40] but was in contrast with high level of awareness found in Southern Nigeria. [41,42] High acceptability of personal screening for haemoglobin genotype among the participants in this study was in keeping with earlier studies in Nigeria [39,43] though poor participation in screening program has also been documented [44].…”
Section: Discussionsupporting
confidence: 87%
“…Results from this study has shown that families understanding of the results provided is still challenging. This observation suggests that despite the high birth prevalence of SCD in the area, still knowledge on the disease is very low (Abioye-Kuteyi et al, 2009;Ezenwosu et al, 2015;Obed et al, 2017;Tutuba et al, 2022). One of the recommendations to address this is to increase public awareness through cultural respectful advocacy campaigns within the communities (Anie et al, 2016;Brown, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…SCD is a haematological non-communicable disease (NCD), sometimes referred to as the invisible NCD [ 2 ]. It is a public health problem that affects around 5% (includes sickle cell trait and sickle cell disease) of the world’s population [ 3 ], with the highest prevalence found in sub-Saharan Africa[ 4 , 5 ]. It is estimated that 15,000 babies are born with this condition every year in Ghana alone [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that primary caregivers of SCD children have higher levels of depression compared to caregivers of their healthy counterparts [ 23 , 24 ]. The studies that have explored SCD caregivers’ perspectives have documented premarital SCD-status knowledge, caregiver action plans during SCD crises, caregiver-SCD-ward relationship dynamics, caregivers’ mental health, coping mechanisms, and burdens of responsibility [ 4 , 25 , 26 ]. Thus, most of the existing research on the capacity of caregivers of SCD children to provide the needed care have concentrated on the psychological domain.…”
Section: Introductionmentioning
confidence: 99%